Living with chronicity and complexity: Lessons for redesigning case management from patients' life stories – A qualitative study - Morales-Asencio, José Miguel; Martín-Santos, Francisco Javier; Kaknani-Uttumchandani, Shakira; Morilla-Herrera, Juan Carlos; Cuevas-Fernández-Gallego, María Magdalena; García-Mayor, Silvia; León-Campos, Álvaro; Morales-Gil, Isabel María (Wiley, 2016)
Abstract Rationale, aims and objectives Case management is commonly used to provide health care for patients with multiple chronic conditions. However, the most effective form of team organization and the necessary support structures need to be identified. In this respect, patients' views could provide a valuable contribution to improving the design of these services. To analyse the experiences of patients with chronic diseases and of caregivers, in relation to health care services and mechanisms, and to identify means of modelling case management services. Methods The method used was a qualitative study based on life stories, and semi-structured interviews with 18 patients with complex chronic diseases and with their family caregivers, selected by purposeful sampling in primary health care centres in Andalusia (southern Spain) from 2009 to 2011. Results Three transition points were clearly identified: the onset and initial adaptation, the beginning of quality-of-life changes, and the final stage, in which the patients' lives are governed by the complexity of their condition. Health care providers have a low level of proactivity with respect to undertaking early measures for health promotion and self-care education. Care is fragmented into a multitude of providers and services, with treatments aimed at specific problems. Conclusions Many potentially valuable interventions in case management, such as information provision, self-care education and coordination between services and providers, are still not provided.
https://openpolicyfinder.jisc.ac.uk/id/publication/7077
Keywords: Enfermos crónicos - Cuidados de enfermería; Investigación cualitativa; Chronic disease; Life change events; Needs assessment; Patient participation; Qualitative research; Case management